In-situ observations of restructuring carbon nanotubes via low-voltage aberration-corrected transmission electron microscopy - Börrnert, F; Bachmatiuk, A; Gorantla, S; Warner, J; Büchner, B; Rümmeli, M (2011)
The molecular structure and dynamics of carbon nanostructures is much discussed throughout the literature, mostly from the theoretical side because of a lack of suitable experimental techniques to adequately engage the problem. A technique that has recently become available is low-voltage aberration-corrected transmission electron microscopy. It is a valuable tool with which to directly observe the atomic structure and dynamics of the specimen in situ. Time series aberration-corrected low-voltage transmission electron microscopy is used to study the dynamics of single-wall carbon nanotubes in situ. We confirm experimentally previous theoretical predictions for the agglomeration of adatoms forming protrusions and subsequent removal. A model is proposed how lattice reconstruction sites spread. In addition, the complete healing of a multi-vacancy consisting of ca. 20 missing atoms in a nanotube wall is followed. © 2011 Materials Research Society.